Analysis of Bacteriological Quality and Antibiogram of Escherichia coli and Staphylococcus aureus in Raw Milk Sold in Janakpurdham (Tribhuvan University Journal of Microbiology, 2025)
Objectives: To assess the microbiological quality of raw milk sold in Janakpurdham, Nepal, by determining the Total Viable Count (TVC) and Total Coliform Count (TCC), isolating Escherichia coli and Staphylococcus aureus, and evaluating its antibiotic susceptibility pattern.Methods: A total of 74 raw milk samples were aseptically collected from dairies and farmers in Janakpurdham from March to June 2025. TVC was determined using the pour plate method on Nutrient Agar, and TCC/E. coli isolation on Eosin Methylene Blue Agar. S. aureus isolation was done on mannitol salt agar after enrichment. Conventional biochemical tests were used to confirm the isolates. Antimicrobial susceptibility of the isolates was performed using the Kirby-Bauer disk diffusion method.Results: Mean TVC was 1.13 × 10⁹ CFU/ml (range: 2.075 × 10⁸–2.76 × 10⁹), and mean TCC was 7.40 × 10⁷ CFU/ml (range: 2.0 × 10⁵–5.28 × 10⁸). E. coli was isolated from all seventy-four samples. Susceptibility was highest to gentamicin (100%) and chloramphenicol (85.13%), but 100% resistance was observed to ampicillin and amoxicillin-clavulanate. 60.81% isolates were multidrug-resistant. S. aureus was detected in 48 samples (65%). Antibiotic susceptibility testing revealed 100% resistance to ampicillin and 72.9% to cefoxitin, while varying resistance was observed for linezolid, erythromycin, clindamycin, and others.Conclusion: Raw milk in Janakpurdham exhibits high microbial contamination and antibiotic-resistant bacteria, posing public health risks; therefore, improved hygiene and antibiotic stewardship are essential.